2017
DOI: 10.1111/cyt.12514
|View full text |Cite
|
Sign up to set email alerts
|

Improving the cytological diagnosis of high‐grade serous carcinoma in ascites with a panel of complementary biomarkers in cell blocks

Abstract: Introduction Precise cytological diagnosis of pelvic high‐grade serous carcinoma (HGSC) in ascites is important for tumour staging, therapeutic decision‐making and prognostic evaluation. However, it can often be difficult to distinguish metastatic HGSC cells from reactive mesothelial cells based on morphology alone. Immunocytochemical analysis of ascites cell blocks has been used to obtain accurate diagnosis and provide a reliable basis for treatment decisions in the clinic. This study was performed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…These authors also stated that current tests for E‐cad lack sensitivity and specificity. Methodologies mainly used for E‐cad protein detection include immunohistochemistry or immunocytochemistry for tissue samples or cell lines, and ELISA tests for biological fluids , these last ones with a declared sensitivity of 0.039 ng mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…These authors also stated that current tests for E‐cad lack sensitivity and specificity. Methodologies mainly used for E‐cad protein detection include immunohistochemistry or immunocytochemistry for tissue samples or cell lines, and ELISA tests for biological fluids , these last ones with a declared sensitivity of 0.039 ng mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Negative staining for MC, CK5/6, and BerEP4 may exclude both mesothelial and epithelial cells 19,20 and positive for WT1, vimentin and negative for CK7 may confirm the diagnosis of OGCT cells, as most OGCT show this kind of immunophenotype. Occasionally, AGCT with a diffuse pattern can be mistaken for a poorly differentiated carcinoma 12,21 . Cytomorphologic features can be very helpful in differential diagnosis as granulosa cells usually show relatively uniform nuclei, and some are often grooved, while poorly differentiated carcinomas with nuclear atypia and mitosis are commonly seen and, usually display hyperchromatic and pleomorphic nuclei without nuclear grooves.…”
Section: Discussionmentioning
confidence: 99%
“…We have postulated that ICC assessments of PAX8, WT1, P53, P16, and Ki‐67 on ascites cytospins and cytoblocks can provide the same information as the primary tumor tissue for the accurate immunophenotyping of HGSC and detection of germline and somatic BRCA1/2 mutations. So far, the sensitivity and specificity of cytopathology for differentiating tumor cells and mesothelial cells in ascites have been proven, 7 yet only a few studies have focused on immunophenotypic features of HGSC. For instance, Bansal et al 12 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Cytospin and cytoblock immunocytochemistry (ICC) has been proven to be highly sensitive and specific for distinguishing HGSC cells from reactive mesothelial cells and other malignant cells in ascites. 7 Yet, it is not clear whether cytoblock ICC can provide an accurate assessment of the immunophenotypic features of HGSC from ascites, and studies on cytospin ICC have not yet been reported. As for the BRCA1/2 status, our group has recently reported that cytopathological specimens (ascites, pleural effusions, and lymph node fine-needle aspirates) of HGSC can be alternatives to primary tumor biopsy for the detection of BRCA1/2 mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation